Proceedings of the 2015 International Conference on Advanced Engineering Materials and Technology 2015
DOI: 10.2991/icaemt-15.2015.162
|View full text |Cite
|
Sign up to set email alerts
|

Hot Ductility of Ti/Nb-added 800MPa Grade Weathering Steel

Abstract: The hot ductility behavior of two kinds of 800MPa grade Ti/Nb-added weathering steel has been investigated by using Gleeble3500 thermo-mechanical simulator. The tensile strength (TS) and reduction in area (RA) were acquired to draw hot ductility curve and hot strength curve. SEM fractographs and microstructures of the tensile specimens were analyzed. The results show that the occurrence of the third brittle zone was related to the formation of film-like ferrite phase along the prior austenite grain boundary. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][38][39][40][41][42] Zhang et al indicated that hot ductility trough resulted from the formation of pro-eutectoid ferrite films along prior austenite grain boundaries. [38,39] The distribution of the impurities [40] or precipitation [39,41] containing Ti, Nb, B, etc. at prior-austenite grain boundaries is another major reason for the obvious loss of hot ductility.…”
Section: A Factors Influencing the Hot Ductilitymentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][38][39][40][41][42] Zhang et al indicated that hot ductility trough resulted from the formation of pro-eutectoid ferrite films along prior austenite grain boundaries. [38,39] The distribution of the impurities [40] or precipitation [39,41] containing Ti, Nb, B, etc. at prior-austenite grain boundaries is another major reason for the obvious loss of hot ductility.…”
Section: A Factors Influencing the Hot Ductilitymentioning
confidence: 99%